EDUKASI USAHA PERIKANAN DAN MANAJEMEN KESEHATAN IKAN YANG BAIK DAN BERKELANJUTAN PADA SISW - Noor, Huriyatul Fitriyah; Jati, Ciptaning Weargo; Santoso, Limin (Program Studi Budidaya Perairan Universitas Mataram, 2025)
This community services program aimed to enhance the competencies of vocational high school students in sustainable aquaculture and fisheries entrepreneurship. The activity was carried out in January 2024 at SMK Negeri 6 Bandar Lampung, involving 10 students from diverse socioeconomic backgrounds. The program covered three core topics: sustainable aquaculture technology, fisheries business development, and fish health management. The implementation utilized a combination of lectures, interactive discussions, and hands-on practical sessions. To measure the effectiveness of knowledge transfer, pre-tests and post-tests were conducted. The results indicated substantial improvements in participants' understanding: comprehension of sustainable aquaculture increased from 2 to 9 participants, fisheries business development from 4 to 10, and fish health management from 3 to 9 participants. These findings suggest that participatory and practice-based learning approaches are highly effective in fostering applied knowledge and skills in the fisheries sector among vocational students.